2022
DOI: 10.3389/fchem.2022.925622
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolized Activated Carbon Anchoring Phosphotungstic Acid as a Recyclable Catalyst for Oxidation of Alcohols With Aqueous Hydrogen Peroxide

Abstract: Keggin-type phosphotungstic acid (HPW) supported on imidazolyl-activated carbon (AC-COIMI-HPW) catalysts was prepared, which was used to catalyze the oxidation of benzyl alcohol with aqueous H2O2. In the presence of AC-COIMI-HPW, the benzyl alcohol conversion of 90.2% with 91.8% selectivity of benzaldehyde was obtained at 90°C for 6 h in an acetonitrile aqueous solution. The catalyst exhibited an outstanding performance for the oxidation of various benzyl alcohols and aliphatic alcohols. In addition, the catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The FTIR spectrum and XRD of activated carbon (AC), phosphotungstic acid supported on imidazolized AC (AC-COIMI-HPW), and ammonium phosphotungstate anchored by imidazolized AC (AC-COIMI-NH4PW) is shown in Figure 1A. The FTIR spectrum of AC in Figure 1A showed that the absorption peaks at 1608 cm −1 and 1400 cm −1 attributed to C=C stretching vibration of the cyclic aromatic skeleton in AC, and there is the characteristic absorption peak of -OH linked at the edge of fused polycyclic aromatic in the bulk of AC at 3130cm In our previous work, it was found that imidazolated nitrogenated activated carbon anchoring phosphotungstate had excellent catalytic performance for benzyl alcohol [24], and the reaction of α-pinene with hydrogen peroxide on ammonium phosphotungstate immobilized on imidazolated nitrogenated activated carbon could selectively convert to sobrerol [25]. In present work, ammonium phosphotungstate anchored by imidazolated nitrogenous activated carbon was developed to catalyze α-epoxypinane ring-opening rearrangement, so as to improve the selective synthesis of carveol and provide a new green [26] catalytic material system from biomass based activated carbon for the preparation of high-value carveol from plentiful and cheap turpentine.…”
Section: Structure and Texture Characteristics Of Catalystsmentioning
confidence: 92%
See 2 more Smart Citations
“…The FTIR spectrum and XRD of activated carbon (AC), phosphotungstic acid supported on imidazolized AC (AC-COIMI-HPW), and ammonium phosphotungstate anchored by imidazolized AC (AC-COIMI-NH4PW) is shown in Figure 1A. The FTIR spectrum of AC in Figure 1A showed that the absorption peaks at 1608 cm −1 and 1400 cm −1 attributed to C=C stretching vibration of the cyclic aromatic skeleton in AC, and there is the characteristic absorption peak of -OH linked at the edge of fused polycyclic aromatic in the bulk of AC at 3130cm In our previous work, it was found that imidazolated nitrogenated activated carbon anchoring phosphotungstate had excellent catalytic performance for benzyl alcohol [24], and the reaction of α-pinene with hydrogen peroxide on ammonium phosphotungstate immobilized on imidazolated nitrogenated activated carbon could selectively convert to sobrerol [25]. In present work, ammonium phosphotungstate anchored by imidazolated nitrogenous activated carbon was developed to catalyze α-epoxypinane ring-opening rearrangement, so as to improve the selective synthesis of carveol and provide a new green [26] catalytic material system from biomass based activated carbon for the preparation of high-value carveol from plentiful and cheap turpentine.…”
Section: Structure and Texture Characteristics Of Catalystsmentioning
confidence: 92%
“…The nitrogen-doped activated carbon-supported phosphotungstic acid catalyst (AC-COIMI-HPW) was prepared according to previous studies [24] (Scheme 2). Generally, the carboxylated activated carbon (AC-COOH) was obtained from the oxidation of activated carbon (AC) with 50% hydrogen peroxide and 12 mol/L −1 H 2 SO 4 aqueous solution at 80 • C, then filtered, washed, and dried.…”
Section: Preparation and Characterization Of Ac-coimi-nh 4 Pw Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the previous operation [27], the preparation of an imidazolized nitrogendoped activated-carbon-supported phosphotungstic-acid catalyst AC-COIMI-NH 4 PW is shown in Scheme 1 and the operational details was carried out: the activated carbon (AC) was oxidized with hydrogen peroxide, replacing corrosive and polluting nitric acid oxidation [28]. Activated carbon (10 g), 30% H 2 O 2 (100 mL,) and 12 mol•L −1 H 2 SO 4 (10 mL) were added to a three-necked flask equipped with a condenser and thermometer and stirred in an oil bath at 70 • C for 2 h. Then the reaction mixture was filtered, washed repeatedly with deionized water until there was no SO 4 2− , and the wet solid material was dried in an oven at 120 • C for 4 h. The collected carboxylated activated carbon is marked AC-O.…”
Section: Catalyst Preparationmentioning
confidence: 99%